2014
DOI: 10.9782/2159-4341-17.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Regular and Support Class Placement and Factors that Contribute to Success of Inclusion for Children with ASD

Abstract: For young children with autism spectrum disorder (ASD) in regular schools, ASD specific service delivery options include regular class placement with itinerant consultative support and support class placement. This study provided an examination of levels of parent, teacher and principal satisfaction with both regular class placement (n = 39) and a satellite support class option (n=35), which provides a more gradual transition into regular class. Given that regular class placement was the ultimate goal for chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Parents expressed the highest preference for special schools known as “resource schools”, which 65% of the parents believed was the optimal type of school (The Autism and Asperger Association 2013 ). Carter et al ( 2014 ) reported that parents and teachers were typically satisfied with special solutions, as well as regular classroom placement. The factors facilitating the education of students with ASD are related to the learning practice and skills of the teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents expressed the highest preference for special schools known as “resource schools”, which 65% of the parents believed was the optimal type of school (The Autism and Asperger Association 2013 ). Carter et al ( 2014 ) reported that parents and teachers were typically satisfied with special solutions, as well as regular classroom placement. The factors facilitating the education of students with ASD are related to the learning practice and skills of the teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Teixeira De Matos and Morgado ( 2016 ) reported that inclusion in mainstream schools is influenced by a positive attitude towards pupils with ASD and their behavior, their attendance in the school or class, and their overall acceptance in groups of typical developing pupils. Carter et al ( 2014 ) reported a high level of satisfaction with special solutions among both parents and teachers, as well as regular classroom placement for children with ASD. Facilitatory factors were found to be related to the learning practice and skills of the teachers, while obstacles were most often linked to the child’s characteristics.…”
Section: Previous Research On Pupils With Asdmentioning
confidence: 99%
“…Physical education (PE) is one school setting in which children with ASD can improve their current level of motor performance as well as gain new skills. Researchers often ask teachers, parents and instructional aids about their experiences with teaching students with ASD but not the individuals themselves (Carter et al, 2014;Schultz, Sreckovic, Able, & White, 2016;Syriopoulou-Delli, Cassimos & Polychronopoulou, 2016). This is one way to examine the how individuals with ASD perceive an experience.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, research regarding academic achievement in the population is less prevalent than research about communication and social skills (Keen, Webster, & Ridley, 2016;Wong et al, 2013). Although students do face barriers to successful inclusion, such as anxiety, poor social skills, adaptability problems, and stereotypical behaviors (Carter et al, 2014;Lindsay et al, 2013), many students with ASD demonstrate shortcomings in core subject areas (Keen et al, 2016;Kurth & Mastergeorge, 2010;Wei, Christiano, Yu, Wagner, & Spiker, 2015). Deficits in reading and math are detected as early as preschool (Miller et al, 2017), and parents report frustration or displeasure with the academic progress for children with ASD (Mackintosh, Goin-Kochel, & Myers, 2012;McDonald & Lopes, 2014;Starr & Foy, 2012).…”
Section: Resultsmentioning
confidence: 99%